2022
DOI: 10.3389/fpsyg.2022.1042234
|View full text |Cite
|
Sign up to set email alerts
|

Promoting participatory research in chronicity: The ESPRIMO biopsychosocial intervention for young adults with multiple sclerosis

Abstract: BackgroundCo-creation allows to develop tailored interventions in chronicity and to increase patients’ engagement. Considering the interacting nature of physical, psychological, and social domains in multiple sclerosis (MS), a biopsychosocial approach to care is crucial.AimsThis paper aims to present (i) an example of a co-creation process in the context of chronic diseases (ii) preferences and perspectives of young adults with multiple sclerosis (YawMS; aged 18–45) and healthcare professionals (HCPs) on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“… 61 Qualitatively exploring the unique perspectives of PwMS and severe gait disability and collecting their suggestions regarding possible barriers and strategies for participation might inform future intervention implementation. 62 Since RAGT is safe and well tolerated by patients with MS, 63 we expect patients to provide positive feedback on the robotic intervention.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Qualitatively exploring the unique perspectives of PwMS and severe gait disability and collecting their suggestions regarding possible barriers and strategies for participation might inform future intervention implementation. 62 Since RAGT is safe and well tolerated by patients with MS, 63 we expect patients to provide positive feedback on the robotic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the ESPRIMO intervention was informed by literature, by YawMS and healthcare professionals ( Donisi et al, 2022 ). This co-creation process may have contributed to the feasibility and acceptability of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol and the ESPRIMO intervention ( Donisi et al, 2021b , 2022 ) had to be adapted to address the challenges of COVID-19 and the related preventative measures enforced by the government; participants’ retention could have been influenced by these change and the pandemic itself. It has been shown that COVID-19 had an impact on clinical research with negative effects on clinical trial initiation, patient enrollment of ongoing trials, protocol adherence, clinical trials’ operations, and data collection ( Lasch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations